Analisis Penilaian Portofolio Dalam Penilaian Hasil Belajar Ipa Di Sekolah Dasar - Ina Magdalena; Euis Suhaibah; Gita Mahardhika; Ummi Latifah; Ryani Husnul Hothimah (CV. ITTC INDONESIA, 2023)
This research analyzes the use of portfolio assessment in evaluating the learning outcomes of Science (IPA) in Elementary School 05 Cipondoh. The method provides a comprehensive overview of students' achievements through the collection, selection, and evaluation of their works. A qualitative approach is employed, involving data collection through classroom observations, interviews, and document analysis. The results indicate that portfolio assessment is effective in measuring students' conceptual understanding, scientific process skills, and critical thinking abilities. However, challenges include the required time and assessment criteria determination. Recommendations include teacher training, objective assessment guidelines, and improved collaboration among teachers, students, and parents.